Factors Associated with the Adoption of Biological Control Agents in Coffee Production in Song District, Phrae Province - Buttapha, Duddao; Seerasarn, Nareerut; Khrutmuang Sanserm, Sineenuch (Journal of Roi Et Rajabhat University, 2026)
This study aimed to 1) examine the socio-economic characteristics of coffee farmers, 2) investigate the use of biological control agents in coffee production, and 3) analyze factors associated with the use of biological control agents among farmers in Song District, Phrae Province. The population consisted of 253 registered coffee farmers for the 2024/2025 production year. A sample size of 155 respondents was determined using Yamane’s formula at a 0.05 level of precision. Data were collected through structured interview questionnaires and analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation, as well as inferential statistics, including cross-tabulation and chi-square tests. The results indicated that the farmers had an average of 3.45 years of experience in coffee cultivation. The average annual agricultural income was 129,368.71 baht, while the average household debt was 49,099.35 baht per year. Most farmers cultivated Robusta coffee and applied Trichoderma spp. to control root rot disease, as well as Beauveria bassiana for insect pest management. However, coffee production was not solely dependent on biological control agents. Key constraints included limited access to reliable sources of biological products, short shelf life of Trichoderma, improper application of Beauveria bassiana, and insufficient training programs and community-based learning centers. It is recommended that relevant agencies provide continuous hands-on training, establish community-based learning centers for biological agriculture, and promote market support for products derived from sustainable agricultural practices.